A farnesol-sensing triad in Pseudomonas aeruginosa drives interkingdom predation on Candida albicans via signal transduction - Zhiyan Wei; Changfu Li; Fengge Song; Xiaoying Zhang; Shuyu Li; Nuoping Xu; Jingchao Zhang; Yan Luo; Yuxin Zuo; Jitong Jiao; Haiyang He; Ruoyi Wang; et al. (Proceedings of the National Academy of Sciences, 2026)
Microbial interactions, particularly bacteria–fungus interactions, are research hotspots within microbial ecology and pathogenic biology. However, their underlying molecular mechanisms remain poorly understood, especially how bacterial pathogens recognize and exploit fungal signaling molecules for fungal predation. Here, we demonstrate that Pseudomonas aeruginosa employs an integrated tripartite farnesol-sensing system to detect and eliminate Candida albicans hyphae: The chemoreceptor PctA mediates directional migration toward hyphae; the type IV pilus sensor PilJ activates antifungal type III secretion system (T3SS) expression; and the quorum regulator PqsR monitors farnesol levels to coordinate virulence-metabolic switching. This mechanism enables bacteria to convert farnesol into their own signaling language ( Pseudomonas quinolone signal) according to fungi status, thereby adaptively modulating their virulence expression and metabolism to cope with complex competitive microbial environments. Furthermore, bioinformatics analysis and functional validation confirm that the PctA–PilJ–PqsR triad is conserved across P . aeruginosa , suggesting that this interkingdom communication is widespread. In conclusion, this study reveals that P . aeruginosa orchestrates a targeted predation strategy against filamentous fungi by coordinating three interkingdom receptors, providing a theoretical foundation and potential molecular targets for understanding of interkingdom communication strategies among microorganisms and the development of signal molecule–based microbial prevention and control technologies.